2020
DOI: 10.1002/app.49979
|View full text |Cite
|
Sign up to set email alerts
|

Engineered polysaccharide alpha‐1,3 glucan asisocyanate‐reactivecomponent in viscoelastic polyurethane foams

Abstract: Enzymatic polymerization is emerging as scalable method to convert sucrose to engineered polysaccharides. Polymer architecture and material properties can be controlled selectively to produce novel differentiated biomaterials. One first example for such an engineered polysaccharide is alpha-1,3-polyglucose (alpha-1,3-glucan) synthesized using glucosyltransferase (GTF) enzymes. Stable dispersions of alpha-1,3-glucan in polyether polyols were prepared with narrow particle size distributions, which are reactive w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Moreover, chitosan is well-known to present natural antibacterial and antifungal properties thanks to the amine groups it contains, which allows the formation of ammonium groups in an acidic environment; thus, cell proliferation and cell adhesion data suggested that the addition of chitosan could be important for the biomedical field. ,, More recently, engineered polysaccharides directly coming from sucrose or glucose have been also explored as alternative polyols for the polyurethane industry. For instance, α-1,3-polyglucose synthesized with glucosyltransferase enzymes has demonstrated to be a suitable reactive component in viscoelastic polyurethane foams …”
Section: Aliphatic Polyether Polyolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, chitosan is well-known to present natural antibacterial and antifungal properties thanks to the amine groups it contains, which allows the formation of ammonium groups in an acidic environment; thus, cell proliferation and cell adhesion data suggested that the addition of chitosan could be important for the biomedical field. ,, More recently, engineered polysaccharides directly coming from sucrose or glucose have been also explored as alternative polyols for the polyurethane industry. For instance, α-1,3-polyglucose synthesized with glucosyltransferase enzymes has demonstrated to be a suitable reactive component in viscoelastic polyurethane foams …”
Section: Aliphatic Polyether Polyolsmentioning
confidence: 99%
“…For instance, α-1,3-polyglucose synthesized with glucosyltransferase enzymes has demonstrated to be a suitable reactive component in viscoelastic polyurethane foams. 128 Finally, the self-condensation of biosourced diols for the production of polyether polyols has also been explored. Traditionally, the production of polyethers by polycondensation has been achieved by Williamson polyetherification via a nucleophilic substitution reaction between an alkoxide and a halogenated alkane.…”
Section: ■ Aliphatic Polyether Polyolsmentioning
confidence: 99%
“…The alpha-1,3 glucan (Scheme ) was obtained by the enzymatic polymerization of glucose derived from sucrose. This reaction is conducted with the use of an enzyme catalyst selected from the general class of glucosyltransferase (GTF) enzymes. The alpha-1,3 glucan generated as such is a water-insoluble, linear, highly crystalline, with a high surface area . Despite their high tendency to form agglomeration, alpha-1,3 glucan can be dispersed in water under shear to form a stable colloidal suspension.…”
Section: Introductionmentioning
confidence: 99%
“…31−33 The alpha-1,3 glucan generated as such is a water-insoluble, linear, highly crystalline, with a high surface area. 34 Despite their high tendency to form agglomeration, alpha-1,3 glucan can be dispersed in water under shear to form a stable colloidal suspension. Furthermore, the enzymatic polymerization process allows the control of morphologies, including spherical aggregates, fibrids, and platelet particles referred to as microcrystalline glucan (MCG).…”
Section: ■ Introductionmentioning
confidence: 99%